Special papersPatent foramen ovale and cryptogenic stroke – a statistical or cause-and-effect relationship? A neurological point of view - Lasek-Bal, Anetta; Puz, Przemysław; Kazibutowska, Zofia (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Patent foramen ovale and atrial septal aneurysm are considered to be factors conducive to the occurrence of stroke and transient ischaemic attacks. However, there is no clear answer to the question whether patent foramen ovale is an independent risk factor for stroke and what the mechanism of potential cerebral ischaemia in patients with an interatrial septal abnormality is. The paper presents the results of studies regarding the issue, including epidemiological, clinical and neuroimaging data. The subject of secondary prevention in patients with cryptogenic stroke and patent foramen ovale, including the results of research into the effectiveness of pharmacological methods and percutaneous closure of interatrial septal defects, is raised. The available research results do not conclusively suggest a causal relationship between patent foramen ovale and stroke. There is a probable summative effect of atrial septal abnormality and other factors (haemostatic and genetic ones as well as those that are associated with cerebral vessels) leading to cerebral ischaemia. There are no indications for the use of anticoagulant treatment in patients with stroke and presence of patent foramen ovale. In patients at a high risk for stroke, invasive treatment should be considered, which is consistent with the position of the European Stroke Organisation.